2020
DOI: 10.3390/agriculture10110519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyacrylamide-Based Super Absorbent Polymer and Corn Straw Biochar on the Arid and Semi-Arid Salinized Soil

Abstract: Green approaches are much more appreciable during the present scenario. Soil amendments are frequently applied for improving water use efficiency, reducing soil salinity in arid and semi-arid areas, controlling the secondary salinization of cultivated soils, and increasing the carbon sequestration capacity of soils. Thus, lab soil column simulation experiments and field experiments were carried out to evaluate these functions of two separate amendments, polyacrylamide-based super absorbent polymer (SAP) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The main component of the filter paper is cellulose, and it is rich in hydroxyl groups, which results in a strong affinity for water molecules. , In addition, cellulose is biocompatible, renewable, biodegradable, nontoxic, and environmentally friendly. Its high specific surface area and good adsorption have been applied in the fabrication and modification of superwetting materials by many studies. , PAM is a general-purpose enhancer of the strength of paper, and it is used often to increase osmosis; also it can act as a flocculant to purify drinking water. , The production process of this material is more convenient and more efficient than has been reported in previous studies . The results of the water-harvesting test showed that the material fabricated in this study has great potential for use in water-harvesting systems.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The main component of the filter paper is cellulose, and it is rich in hydroxyl groups, which results in a strong affinity for water molecules. , In addition, cellulose is biocompatible, renewable, biodegradable, nontoxic, and environmentally friendly. Its high specific surface area and good adsorption have been applied in the fabrication and modification of superwetting materials by many studies. , PAM is a general-purpose enhancer of the strength of paper, and it is used often to increase osmosis; also it can act as a flocculant to purify drinking water. , The production process of this material is more convenient and more efficient than has been reported in previous studies . The results of the water-harvesting test showed that the material fabricated in this study has great potential for use in water-harvesting systems.…”
Section: Introductionmentioning
confidence: 67%
“…27,28 PAM is a general-purpose enhancer of the strength of paper, and it is used often to increase osmosis; also it can act as a flocculant to purify drinking water. 29,30 The production process of this material is more convenient and more efficient than has been reported in previous studies. 31 The results of the water-harvesting test showed that the material fabricated in this study has great potential for use in water-harvesting systems.…”
Section: ■ Introductionmentioning
confidence: 90%
“…PAM hydrogels are also frequently used as soil amendments to improve water use efficiency and reduce soil salinity. In [ 53 ], lab soil column simulation experiments and field experiments were carried out to evaluate these functions of two separate amendments, polyacrylamide-based super absorbent polymer (SAP) and corn straw biochar at different application rates. The simulation experiments showed that both SAP and biochar inhibited the accumulation of soil salinity, with a reduced rate of 9.7–26.3% and 13.5–37.2%, respectively, dependent on the amendment application rates.…”
Section: Superabsorbent Polymer Hydrogelsmentioning
confidence: 99%
“…Persistent in the environment and able to retain water, nutrients, and contaminants, biochar can be used as a soil conditioner for improving soil health, enhancing fertilizer use efficiency, promoting plant growth, and reducing greenhouse gas emission (Guo et al, 2016a;. Biochar may also be used in environmental rehabilitation such as remediation of saline soils and reclamation of abandoned mine land through its high capacity for contaminant immobilization (Feng et al, 2020;Guo et al, 2016a). Biochar filters are suitable for onsite wastewater treatment (Perez-Mercado et al, 2018;Dalahmeh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%